Efficacy and Safety of Apatinib Treatment for Advanced Cholangiocarcinoma After Failed Gemcitabine-Based Chemotherapy: An Open-Label Phase II Prospective Study - Zhang, Ge; Gong, Shuai; Pang, Lina; Hou, Lixia; He, Wei (Frontiers in Oncology, 2021)
Purpose As a novel small-molecule vascular endothelial growth factor receptor-2 tyrosine kinase inhibitor (VEGFR2-TKI), Methylsulfonic apatinib (apatinib) exhibits a specific antitumor effect in various solid tumors via inhibition of angiogenesis. The present study was performed to evaluate the clinical efficacy and safety of apatinib in the treatment of advanced cholangiocarcinoma after failed gemcitabine-based chemotherapy. Patients and Methods This was a prospective open-label phase II trial (NCT03521219). A total of 32 patients, in whom gemcitabine-based first-line chemotherapy for advanced intrahepatic cholangiocarcinoma had failed, were consecutively enrolled in a prospective, open, exploratory, and single-center clinical trial from November 2017 to November 2018. They were treated with apatinib mesylate second-line monotherapy (orally, 500 mg per day for a cycle of 28 days) until progressive disease or unacceptable toxicity. Using Response Evaluation Criteria in Solid Tumor version 1.1 (RECIST 1.1) and the Common Terminology Criteria for Adverse Events version 4.0 (NCI-CTCAE 4.0), the efficacy and adverse were evaluated, respectively. Kaplan-Meier method was used for survival analysis. Results Twenty-six patients were enrolled in full analysis set. At the end of follow-up, two patients were lost to follow-up, 24 of 26 patients in FAS were included in efficacy analyses. For the efficacy analysis set, the objective response rate (ORR) was 20.8% [95% confidence interval (CI): 9.24–40.47%] and the disease control rate (DCR) was 62.5% (95% CI: 112.86–387.14 days). One patient (4%) showed complete response (CR), 4 patients (17%) showed partial response (PR), 10 patients (41.7%) stable disease (SD), and 9 patients (37.5%) had progressive disease (PD). Meanwhile, apatinib therapy achieved the median progression-free survival PFS was 95 days (95% CI: 79.70–154.34 days), and the median OS was 250 days (95% CI: 112.86–387.14 days). Furthermore, univariate analysis revealed that age and tumor’s anatomic location significantly affected PFS (P < 0.05). The most common clinically adverse events (AEs) included myelosuppression (69.2%), hypertension (57.7%), proteinuria (46.2%). The AEs were mild, mainly in grade 1 or 2, and no toxicity-induced death occurred. Conclusion Apatinib monotherapy is an effective and promising regimen for treating patients with advanced cholangiocarcinoma who experienced failure of gemcitabine-based chemotherapy.